Mechanism-based tuning of insect 3,4-dihydroxyphenylacetaldehyde synthase for synthetic bioproduction of benzylisoquinoline alkaloids - Christopher J. Vavricka (Nature Communications, 2019)
Bioproduction of tetrahydropapaveroline (THP) is limited by the specificity of monoamine oxidase (MAO). Here, the authors identify an insect 3,4-dihydroxyphenylacetaldehyde synthase (DHPAAS) that can bypass MAO for direct aldehyde production and demonstrate bifunctional switching of DHPAAS for efficient THP production.